CONFLICTS IN THE MANAGEMENT OF ECONOMIC RESOURCES OBTAINED BY RIGHT OF EASEMENT IN THE PEASANT COMMUNITY OF RACCAYA (YEAR 2019-2020) - Llocclla Rodriguez, Eber (2024)
This research seeks to describe, analyze and explain the conflict generated in the rural community of Raccaya by the management of economic resources from easement rights that the mining company pays to the community. Delimited in the management of the communal directive of the year 2019 and 2020. Since 2005, the “Catalina Huanca” mining company has been paying a monthly amount to the community for easement rights, that is, for the use of surface land for mining activities; however, this was changed in 2012, increasing exponentially, presenting a community with a lot of money in proportion to the number of inhabitants it has. The research details the relationship between the management of economic resources obtained through easement rights and the conflict within the community, and the main factors that influence it. For this purpose, the approachused was qualitative, highlighting the ethnographic method to obtain information, in addition to interviews and documentary review of the community. The main evidence is that there is a direct relationship between the way in which the community’s money received by right of servitude is managed and the conflicts between the settlers and their authorities. The most important factors are the lack of planning, excessive distrust of the communal board of directors, lack of consensus in the general assembly, and the absence of oversight within the community’s statutes. This reality is reflected in the fact that the communal authorities do not have the capacity to manage development projects or activities in favor of the common good, in the same way the population does not have the competencies to manage their economic income in a sustainable way, that is to say, the rural community of Raccaya manages its money in an inefficient and improvised way without any development plan in a context of conflict among its members.